CONTRIBUTION OF INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) TO IMPROVE HALAL FOOD IN THAILAND - Anantakupa, Azhar Gusti (PT. Jurnal Center Indonesia Publisher, 2025)
The Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) is an important factor in the development of the halal food and industry sector in Thailand. Through collaborative efforts that promote knowledge sharing and best practices, technological advancements that enhance efficiency and transparency, regulatory frameworks that facilitate trade, and capacity-building initiatives that empower local enterprises, the Indonesian government has been able to enhance the quality and competitiveness of its products on the global market by sharing successful experiences and tactics in halal certification, product monitoring, and regulation. In this study, we adopted a qualitative approach to examine the contribution of the Indonesia-Malaysia-Thailand Growth Triangle in improving the quality of the food industry in Thailand. The qualitative findings provided a theoretical framework and conceptual dimensions, enhancing the understanding of how IMT-Growth Triangle initiatives influence the development and management of a sustainable dietary system in Thailand from the very beginning.